Networks and Geographies of Global Social Policy Diffusion Culture, Economy, and Colonial Legacies - Windzio, Michael; Mossig, Ivo; Besche-Truthe, Fabian; Seitzer, Helen (Global Dynamics of Social Policy, 2022)
This open access book analyses the global diffusion of social policy as a process driven by multiplex ties between countries in global social networks. The contributions analyze links between countries via global trade, colonial history, similarity in culture, and spatial proximity. Networks are viewed as the structural backbone of the diffusion process, and diffusion is anlaysed via several subfields of social policy, in order to interrogate which network dimensions drive this process. The focus is on a global perspective of social policy diffusion via networks, and it is the first book to explicitly follow this macro-quantitative perspective on diffusion at a global scale whilst also comparing different networks. The collection tests the network structures in terms of their relevance to the diffusion process in different subfields of social policy such as old age and survivor pensions, labor and labor markets, health and long-term care, education and training, and family and gender policy. The book will therefore be invaluable to students and researchers of global social policy, sociology, political science, international relations, organization theory and economics.